2012
DOI: 10.5047/eps.2011.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Ion distributions in the vicinity of Mars: Signatures of heating and acceleration processes

Abstract: More than three years of data from the ASPERA-3 instrument on-board Mars Express has been used to compile average distribution functions of ions in and around the Mars induced magnetosphere. We present samples of average distribution functions, as well as average flux patterns based on the average distribution functions, all suitable for detailed comparison with models of the near-Mars space environment. The average heavy ion distributions close to the planet form thermal populations with a temperature of 3 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 36 publications
6
59
0
Order By: Relevance
“…The planetary ions are gradually accelerated to escape energies throughout the tail. At Mars studies have shown that a low energy tailward drifting component is dominating large parts of the tail (Nilsson et al, ). The situation in Venus's magnetotail is complicated as there is a substantial flow of ions returning toward Venus (Kollmann et al, ; Persson et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The planetary ions are gradually accelerated to escape energies throughout the tail. At Mars studies have shown that a low energy tailward drifting component is dominating large parts of the tail (Nilsson et al, ). The situation in Venus's magnetotail is complicated as there is a substantial flow of ions returning toward Venus (Kollmann et al, ; Persson et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Nilsson et al [] have estimated the tailward flux escape inside the nominal Induced Magnetospheric Boundary as a function of the tail distance. The average value is 1.1 × 10 24 s −1 , while the total escape is estimated to be equal to 2.2 × 10 24 s −1 .…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The absence of an EUV dependence for fluxes of ions with E > 30 eV was one of the reasons for separation of ions into high‐ and low‐energy components. Moreover, such a separation is natural that is confirmed by analysis of ion distribution functions in the Martian tail [ Nilsson et al , ; Fraenz et al , ]. Note that the real energy of the low‐energy oxygen ions is usually lower since the ions in the tail are additionally accelerated by the spacecraft potential.…”
Section: Observationsmentioning
confidence: 86%